An Overview of Sinkhole Geohazard Incidence Recorded in The Kinta Valley Area, Perak - Ahmad Khairut Termizi; Tuan Rusli Tuan Mohamed; Rodeano Roslee (2018)
This paper is prepared to provide an overview of the sinkholes geohazards that occurs quite often in the Kinta Valley area. By fact, the phenomenon of the sinkhole is a common in Kinta Valley as its compound in karsts environment with limestone bedrock underlain about 80% of the area. The occurrences of sinkholes always affected badly on urban development and caused economic loses to the owner or landlord. The record regarding the sinkholes in pass days was started informally through shorthand in the log book and personal diaries. Since the cases arose, Minerals and Geoscience Department of Malaysia (JMG-Malaysia) started proper documentation in year 1970s and until February 2012 there were 161 incidents and 288 sinkholes were recorded surrounding Kinta Valley. Preliminary interpretation shows that the development of sinkhole associated to the factors of subsurface geology, historic of site activities which related to mining, current land used status, also seasonal drastic change between dry and wet spell in local climate.